The effect of workload on burnout mediated by work-family conflict among employees - Nurul Huda; Herning Indriastuti (Privietlab, 2026)
This study analyzes the effect of workload on burnout, with Work-Family Conflict (WFC) as a mediating variable, among employees of Bank Rakyat Indonesia (BRI) Branch Office Samarinda 1. The study is grounded in the growing pressure faced by banking employees, including high service demands, extended working hours, strict accuracy requirements, and performance targets that may intensify psychological strain. A quantitative research design was applied using a saturated sampling technique, involving all 84 employees as respondents. Data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.1. The findings reveal that workload has a positive and significant effect on burnout and WFC. WFC also has a positive and significant effect on burnout. Furthermore, WFC partially mediates the relationship between workload and burnout, indicating that excessive workload increases burnout both directly and indirectly by disrupting employees’ balance between work and family roles. These results highlight the importance of workload management, adequate staffing, realistic performance targets, and family-supportive policies to reduce burnout risk. The study contributes to human resource management literature by providing empirical evidence from an Indonesian banking branch context. It also offers practical guidance for managers seeking to sustain employee well-being and service quality.